Governance structures for competition policy a case study of the Philippines - Cabalu, Helen; Kenyon, Peter; Koshy, Paul; Will-Johnson, Nick (The Philippine Review of Economics, 2006)
Competition policy has become one of the key elements of national economic policy in many countries around the world. This is due to the important role that competition plays in ensuring that markets efficiently produce goods and services that best meet evolving consumer demands. This paper explores the rationale for a comprehensive competition policy and sets out the principles of governance and a suggested governance structure that would deliver an effective competition policy in the Philippines. It also explores the difficulties in implementing competition policy in a developing country where public policy governance structures are not well resourced.